Music therapy promotes self-determination in young people with autism spectrum disorder. Issue 2 (2nd April 2016) - Gadberry, Anita L.; Harrison, Angela
Abstract : Self-determination leads to a higher quality of life, yet many individuals with autism spectrum disorder struggle with the component skills necessary for self-determination. Music therapy is one method of treatment for persons with autism spectrum disorder and has the ability to improve or develop skills in communication, self-awareness, socialization, and decision making. Two components of evidence-based practice (clinical expertise and scientific research) are presented in this article describing how music therapy facilitates self-determination.